Application of Contextual Approach in Improving Computational Operation Skills in Students with Learning Delays - Puteri, Novita Cahyo; Leonard, Leonard; Astuti, Natalia Tri (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
This study aims to analyze and determine the effect of applying the contextual approach in improving the ability of calculation operations in students with learning delays. This study uses a quantitative approach with a single-subject experiment method, often called Single Subject Research (SSR), with an A-B-A design. The subject of this study is grade VIII students at SMP Islam Mandiri. The data collection technique in this study was carried out using observation and a test of computational operation ability. The results of the baseline-1 phase showed a stable score and increased when the treatment was carried out in the intervention phase; after the treatment was carried out, the research subjects were then given a test in the baseline-2 phase, and the results obtained increased with a score of 100 in each session. The percentage overlap of the three phases is at the level of 0%. Thus, the results show that applying the contextual approach positively improves the ability to calculate operations in students with learning delays.